ANALISIS KELEMBAGAAN PENGELOLAAN HUTAN PRODUKSI DI UPTD KEHUTANAN MUNA UTARA I DINAS KEHUTANAN KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - Rufendi, Muhamad; Rianda, La; Padangaran, Ayub M (Universitas Halu Oleo, 2016)
This study was conducted at Lambiku village in Napabalano sub district of Muna regency. The aims of the study were: (1) to find out the process of planning and implementing Hutan Tanaman Rakyat (HTR) developmental program at Lambiku village in Napabalano sub district of Muna regency; (2) to find out the effectiveness level of the implementation of Hutan Tanaman Rakyat (HTR) developmental program at Lambiku village in Napabalano sub district of Muna regency.Â The study used a descriptive analysis to describe the process involved in the planning and implementation of HTR program at Lambiku village, as well as an effectiveness analysis to compare the planning and the implementation of HTR program at Lambiku village. The study employed a survey method and direct interview related to HTR program in Muna regency, as well as collected other supporting data from relevant institutions. Results of the survey and data collection were then described in accordance with the purpose of the study. The only location of HTR in Muna regency that has obtained the Permission for Utilizing Forest Wood Products from Hutan Tanaman Rakyat is Lambiku village in the sub district of Napabalano. There are 10 holders of IUPHHK-HTR in Lambiku village, with a total area of 63 hectares.Â The planning of HTR program in Lambiku village of Napabalano sub district has been done in accord with prevailing regulations. The implementation of HTR program in Lambiku village has not been fully effective. It is important to optimize the performance those mentoring the HTR.Keywords: planning of HTR, implementation of HTR, effectiveness